2012
DOI: 10.3389/fimmu.2012.00355
|View full text |Cite
|
Sign up to set email alerts
|

Immune Reconstitution and Graft-Versus-Host Reactions in Rat Models of Allogeneic Hematopoietic Cell Transplantation

Abstract: Allogeneic hematopoietic cell transplantation (alloHCT) extends the lives of thousands of patients who would otherwise succumb to hematopoietic malignancies such as leukemias and lymphomas, aplastic anemia, and disorders of the immune system. In alloHCT, different immune cell types mediate beneficial graft-versus-tumor (GvT) effects, regulate detrimental graft-versus-host disease (GvHD), and are required for protection against infections. Today, the “good” (GvT effector cells and memory cells conferring protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 158 publications
(180 reference statements)
1
9
0
Order By: Relevance
“…These data were corroborated by the significant increase in the expression of iNos, Pges, Cox-2, and Tgf-b. Because the production of such molecules ultimately leads to the inhibition of T cell proliferation [62,63], we confirmed the preliminary observations testing the effect of CSCL in supporting the inhibition of PHA-stimulated PBMC proliferation in a cell-cell contact assay. The functional study confirmed the greater immunosuppressive potential of MSCs grown onto CSCL yet suggested a lower immunogenic capability of MSCs when CS is not included in the system.…”
Section: Discussionsupporting
confidence: 80%
“…These data were corroborated by the significant increase in the expression of iNos, Pges, Cox-2, and Tgf-b. Because the production of such molecules ultimately leads to the inhibition of T cell proliferation [62,63], we confirmed the preliminary observations testing the effect of CSCL in supporting the inhibition of PHA-stimulated PBMC proliferation in a cell-cell contact assay. The functional study confirmed the greater immunosuppressive potential of MSCs grown onto CSCL yet suggested a lower immunogenic capability of MSCs when CS is not included in the system.…”
Section: Discussionsupporting
confidence: 80%
“…Most of preclinical data have emerged from mice models, which are useful to design preventive strategies ( 4 ), although they imperfectly reflect the disease observed in humans ( 5 ). However, other experimental models such as rat models are also used ( 6 ). The indispensible prerequisite to properly assess the efficacy of a therapeutic approach of aGVHD is to be able to efficiently and easily evaluate and grade the intensity and/or severity of this condition throughout the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…As was recently outlined by Zinöcker et al alloreactive donor NK cells in a MHC class I disparate setting could also facilitate engraftment and donor reconstitution and therefore could have positive influence on establishing chimerism [30].…”
Section: Plos Onementioning
confidence: 90%